2020
DOI: 10.1371/journal.pone.0239602
|View full text |Cite
|
Sign up to set email alerts
|

Association between chronic obstructive pulmonary disease (COPD) and occupational exposures: A hospital based quantitative cross-sectional study among the Bangladeshi population

Abstract: The association between chronic obstructive pulmonary disease (COPD) and occupational exposures are less studied in Bangladeshi context, despite the fact that occupational exposures are serious public health concerns in Bangladesh. Therefore, this study aimed to evaluate this association considering demographic, health and smoking characteristics of Bangladeshi population. This was a hospital-based quantitative study including 373 participants who were assessed for COPD through spirometry testing. Assessment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…In a study published in 2016, occupations that were at COPD risk were seafarers, coalmine operatives, and cleaners [ 12 ]. In a study in Bangladesh, occupational exposures in farmers, hazardous exposures in tanners, and cotton dust exposures in garments were among the most prominent risk factors for the development of COPD [ 13 ]. In our study, the urban population comprised the majority (57.8%, Table 2 ), which correlates well with a study done in India where the prevalence of COPD was more in the urban areas.…”
Section: Discussionmentioning
confidence: 99%
“…In a study published in 2016, occupations that were at COPD risk were seafarers, coalmine operatives, and cleaners [ 12 ]. In a study in Bangladesh, occupational exposures in farmers, hazardous exposures in tanners, and cotton dust exposures in garments were among the most prominent risk factors for the development of COPD [ 13 ]. In our study, the urban population comprised the majority (57.8%, Table 2 ), which correlates well with a study done in India where the prevalence of COPD was more in the urban areas.…”
Section: Discussionmentioning
confidence: 99%
“…The authors of a recently published systematic review and meta‐analysis from India reported a 7% prevalence of COPD among the population aged 50 years and above; among others, biomass fuel exposure was an important risk factor 2 . There was a 6.3 times higher risk of COPD among workers such as mechanics, cleaners and others with self‐reported exposure to vapours, gas, dust, fume and smoke in their workplace than the non‐exposed group in a small hospital‐based study from Bangladesh 3 …”
Section: Figurementioning
confidence: 97%
“…2 There was a 6.3 times higher risk of COPD among workers such as mechanics, cleaners and others with self-reported exposure to vapours, gas, dust, fume and smoke in their workplace than the non-exposed group in a small hospital-based study from Bangladesh. 3 Recent reports from developed countries list industrial exposures to metal dusts, sand and synthetic resins and other dusts generated due to activities such as smelting, machine maintenance, casting and finishing as causes of occupational COPD. 4 On the other hand, reports from India and several other countries in the subcontinent show exposures to household work, occupational and agricultural dusts and indoor and outdoor pollution as having a significant association with COPD (Table 1; Figure 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To set the backdrop, a pre-pandemic summary of these countries' socio-economic and demographic relevant factors for COVID-19 is presented in [17,18], COPD [19][20][21][22][23], asthma [24][25][26][27][28], diabetes (Adults), cardiovascular death rate, no of hospital beds, and number of people in different age groups and GDP per capita (2019 and 2020) for each of the five countries. Population in each category reported in millions.…”
Section: Introductionmentioning
confidence: 99%